2005
DOI: 10.1207/s15328015tlm1703_3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Training of Internal Medicine Residents in Advanced Cardiac Life Support Protocols: A Randomized Trial

Abstract: Performance improved significantly after simulator training. No improvement was detected as a function of clinical experience alone. The educational program was rated highly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
166
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(184 citation statements)
references
References 22 publications
12
166
2
4
Order By: Relevance
“…Prior studies have evaluated the feasibility of virtual simulation and the effects of simulation on teamwork [2,3], and these studies have found a positive effect on team dynamics via these simulation methods, similar to our study. To our knowledge, no studies have examined the feasibility of long-distance, remote simulation to improve teamwork.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Prior studies have evaluated the feasibility of virtual simulation and the effects of simulation on teamwork [2,3], and these studies have found a positive effect on team dynamics via these simulation methods, similar to our study. To our knowledge, no studies have examined the feasibility of long-distance, remote simulation to improve teamwork.…”
Section: Discussionsupporting
confidence: 86%
“…Clinical experience alone has not been associated with improved team performance [5]; therefore, training programs are focusing on team dynamics during medical crises as a point of improvement. Since team dynamics can be taught and practiced in simulated environments [6,7], various types of simulation have been developed – computer-based, manikin, and standardized patient [2,3,8]. These training tools may not be available in many hospitals and training facilities in low-middle income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Our data support prior work showing that procedural skills that are poor at baseline can be increased significantly using simulation-based training and deliberate practice. [11][12][13][14][15][16][17][18]28 This report on CVC insertion adds to the growing body of literature showing that simulation training complements standard medical education, [11][12][13][14][15][16][17][18][19]28 and expands the clinical application of the mastery model beyond thoracentesis and ACLS. 11,12 Use of the mastery model described in this study also has important implications for patients.…”
mentioning
confidence: 99%
“…29,30 Residents more frequently follow standardized resuscitation measures during actual events after receiving training that utilizes simulation and deliberate practice. 31,32 Using simulation for procedural skill training improves pediatric residents' short-term skill retention. 33 Feedback is often quite variable and inconsistent after resident training experiences, and is generally dependent on individual educators whose own experiences may be limited.…”
Section: Discussionmentioning
confidence: 99%